Association between media exposure and behavioral problems among preschool children - Zoromba, Mohamed A.; Abdelgawad, Doaa; Hashem, Sahar; El-Gazar, Heba; Abd El Aziz, Magda Ahmed (Frontiers in Psychology, 2023)
Background: The prevalence of behavioral problems among preschool children is remarkably increasing in the clinical setting. Aim: The current study aimed to investigate the association between media exposure and behavioral problems among preschool children. Methods: This survey study recruited 560 children from 10 nurseries selected randomly, located in El-Mansoura, Egypt. Tools included socio-demographic characteristics the Media Exposure Questionnaire and the Conners Comprehensive Behavior Rating Scales (CBRS-48). Results: The participants were exposed to media for an average of 105.84 min per day and displayed moderate levels in all subscales of CBRS-48. The duration of media exposure was significantly correlated to the hyperactivity index, learning problems, hyperactivity/impulsivity, conduct problem, anxiety, and psychosomatic problems (r = .372, .356, .323, .306, .298, .291, and .255, respectively). Conclusion: The duration of media exposure was significantly correlated to the subscales of CBRS-48. Implication for nursing practice: Preschool children should be engaged in concrete activities and social interactions that may lessen negative media effects such as hyperactivity, learning problems, hyperactivity/impulsivity, conduct problem, anxiety, and psychosomatic problems.